Extending the Operation of Existing Biogas Plants: Which Follow-Up Concepts and Plants Will Prevail? - Güsewell, Joshua; Scherzinger, Katharina; Holstenkamp, Lars; Vincent, Lynn; Eltrop, Ludger (Frontiers in Energy Research, 2021)
For the existing biogas plants (BGP) in Germany, the period of the public support scheme begins to end in 2021. From a technical point of view, essential components have an operational life span of more than 20 years and allow for an extended operation. However, a profitable extension would require suitable follow-up concepts and depends on the underlying plant-specific setup, the regional conditions as well as the regulatory and economic framework. Based on an expert evaluation, four promising follow-up concepts were identified in a multistage process consisting of expert interviews, workshops, and an online survey. These follow-up concepts are ‘Basic flexibilization’, ‘Substrate change’, ‘Seasonal flexibilization’, and ‘Biomethane upgrading’. They were assessed with a plant-specific biogas repowering model for a heterogeneous data set of 2,508 BGPs and were compared in three scenario frameworks to derive robust development paths. To capture the heterogeneity of the existing BGPs in Germany, the model was developed further regarding regional parameters such as power output, substrate mix, and emission factors. Across all scenarios, ‘Seasonal flexibilization’ proves to be the most promising follow-up concept for more than 50% of the BGPs. This is followed by ‘Substrate change’, which is particularly suitable for larger BGPs with high shares of energy crops and no heat utilization. Biomethane upgrading is usually the second choice compared to participation in extended public support schemes for electricity production. However, it is the only concept that is profitable under current market conditions due to the high CO2-quota prices in the German fuel sector. The development pathways also show a significant potential to increase the net GHG reduction, which on BPG average can be nearly doubled. Our approach shows that the interplay of the heterogeneous BGP structure, the applied economic decision variable, and the non-uniform framework conditions in different energy markets is of crucial importance when assessing similar biogas markets, identifying robust follow-up pathways, or designing framework policies.